2022
DOI: 10.3390/antiox11101972
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Gliosis in Obesity, and the Role of Antioxidants as a Therapeutic Alternative

Abstract: Obesity remains a global health problem. Chronic low-grade inflammation in this pathology has been related to comorbidities such as cognitive alterations that, in the long term, can lead to neurodegenerative diseases. Neuroinflammation or gliosis in patients with obesity and type 2 diabetes mellitus has been related to the effect of adipokines, high lipid levels and glucose, which increase the production of free radicals. Cerebral gliosis can be a risk factor for developing neurodegenerative diseases, and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 201 publications
1
3
0
Order By: Relevance
“…When Ldlr-/-.Leiden mice were fed an obesity-inducing HFD, these pathological features remained. Neurodegeneration and astrogliosis are key features of obesity-related brain histopathology as described in both humans and mice (Thaler et al, 2012;Guillemot-Legris and Muccioli, 2017;Bondan et al, 2019;Bandala et al, 2022). In this study, neurodegeneration was prominently observed in the thalamus.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…When Ldlr-/-.Leiden mice were fed an obesity-inducing HFD, these pathological features remained. Neurodegeneration and astrogliosis are key features of obesity-related brain histopathology as described in both humans and mice (Thaler et al, 2012;Guillemot-Legris and Muccioli, 2017;Bondan et al, 2019;Bandala et al, 2022). In this study, neurodegeneration was prominently observed in the thalamus.…”
Section: Discussionsupporting
confidence: 59%
“…This process, known as astrogliosis, is characterized by an extensive synthesis of glial fibrillary acidic protein (GFAP) (Eng and Ghirnikar, 1994;Sofroniew, 2009). In both humans and rodents, obesity-induced astrogliosis was notably shown in the hypothalamus, as well as other parts of the brain such as the cortex and the hippocampus (Thaler et al, 2012;Guillemot-Legris and Muccioli, 2017), which is also accompanied by an increase in GFAP immunoreactivity (Guillemot-Legris and Muccioli, 2017;Bondan et al, 2019;Bandala et al, 2022). Obesity-related astrogliosis has been associated with neuroinflammation, which is characterized by microglia activation.…”
Section: Introductionmentioning
confidence: 99%
“…They explained that this positive association between BMI and brain glucose metabolism might be due to neuroinflammation and astrogliosis [ 8 ]. Indeed, obesity is known to be related to gliosis [ 20 , 21 ], and several studies have reported that higher astrocytic reactivity is related to higher F-18 FDG uptake [ 22 , 23 ]. These conflicting results may be explained by sex.…”
Section: Discussionmentioning
confidence: 99%
“…Он возникает при ожирении и в основном происходит в гипоталамусе, вызывая потерю нейронов в медиобазальном гипоталамусе, который широко связан с инфундибулярным ядром или аркуатным ядром гипоталамуса, ответственным за функции, связанные с весом и энергетическим гомеостазом. В этих структурах мозга расположены нейроны, отвечающие за энергетический баланс, продуцирующие ПОМК, агути белок и НПY [20].…”
Section: разделunclassified